If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6h + -3 = -9 Reorder the terms: -3 + 6h = -9 Solving -3 + 6h = -9 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 6h = -9 + 3 Combine like terms: -3 + 3 = 0 0 + 6h = -9 + 3 6h = -9 + 3 Combine like terms: -9 + 3 = -6 6h = -6 Divide each side by '6'. h = -1 Simplifying h = -1
| -15v+9=-20v-9 | | 10p-45=3(b-15) | | 58454+n=58454 | | 7g+9=44 | | (x)(4x)=192 | | 3x-21+5x=16+6x-11 | | 2a-3b+1=0 | | 3f-27=-3 | | 3y-6=18-y | | 4x-2x(4+6)=-22 | | 4.9t^2+4t-50=0 | | 8e+5=21 | | 6(z-4)=12 | | 4x+9y+3(x+y)= | | 2/3x+4=7/3x-12 | | 3d+7=-11 | | 72=8(s-2) | | 2x=7x+5 | | 72=8(-2) | | 2k+21=35 | | 4secx+9=0 | | 6(5-8x)+12=-5x | | (2a-3b+1)=0 | | 5(v+1)=7v-15 | | -6.9(4t+6)-2.9(3t-5)= | | 12x=2(x+10) | | 5t-3t-14=0 | | 3x-4=2(2x+6) | | 2c-5=15 | | 44+20=h | | P+p+o=4 | | 12-s=14 |